Return to education and financial value of investment in higher education in Indonesia - Yubilianto (Journal of Economic Structures, 2020)
While there is extensive literature discussing the return to education using the remarkable semi-log Mincer equation, very few studies utilize the full discounting method to examine the impact of education investment from an individual perspective. This paper tries to analyze the return to higher education in Indonesia through the full discounting method mainly using the Indonesia Family Life Survey wave 5 (IFLS-5) and Synthetic Work-life Earnings (SWE) estimation. The results indicate that the median college graduate workers earn about 60% higher salary than that of secondary school leavers. With 4 years to complete a college degree, this figure indicates that the return to higher education is implicitly around 15%, which is similar to the result of the Mincer earnings equation analysis. Moreover, it takes at least 14 years of working time to compensate for the investment in getting a bachelor's degree. These findings suggest that households should consider spending their money for university education. Likewise, the government and financial institutions can provide a better loan policy for higher education.
Keywords: 330; Return to education; The full discounting method; Indonesia Family Life Survey (IFLS); Synthetic work-life earnings (SWE) estimate